Webizing Mixed Reality for Cooperative Augmentation of Life Experience - Seo, Daeil; Yoo, Byounghyun; Ko, Heedong (PROCEEDINGS OF THE 19TH ACM CONFERENCE ON COMPUTER SUPPORTED COOPERATIVE WORK AND SOCIAL COMPUTING COMPANION, 2016)
Most mixed and augmented reality (MAR) applications require the target to be specified a priori and need the same MAR applications among cooperative users. Thus, most existing MAR applications are hard to share MAR scenes or contents without prior agreement for cooperative works. To address this problem, we propose a webizing method that redesigns component relationship of MAR content using an episode as a container of user interactions for sharing life experience and activities. The MAR scene can be gradually developed by multiple participants of the episode. Our examples demonstrate MAR contents can be cooperatively produced, accumulated and consumed like Web 2.0, a digital prosumption that has proven effective in dramatic expansion of Web contents.